ANALISIS KOMPETENSI DAN KESELARASAN PENGGUNA LULUSAN DALAM PELAKSANAAN TRACER STUDY IST AKPRIND YOGYAKARTA - Nur Rahmawati; Eska Almuntaha; Agus Hindarto Wibowo; Erna Kumalasari Nurnawati (Jurnal Signaling, 2022)
Tracer study results is used to make meaningful decisions regarding study design and practical solutions based on tracer study results. The results of the tracer study conducted at IST AKPRIND provide many benefits because apart from being monitoring, the tracer study also serves as feedback for study programs and institutions to evaluate and support an independent learning curriculum so that graduates can meet the needs of society and the demands of the world of work. Currently, the implementation of tracer studies at IST AKPRIND is carried out by each study program. Data collection and coordination of tracer studies are carried out by the Student Administration Section. Although not optimal, IST AKPRIND continues to make improvements and innovations to obtain the desired data. With the assistance of the tracer study facilitation program which was organized by the Directorate General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia, it’s hoped that response rate will increase. The research method used is a quantitative method through the distribution of questionnaires were distributed to graduates throughout 2019 and 2020. The results of the study explain that the competencies possessed by graduates are in accordance with the needs of the world of work and the relevance or linkage between the fields between the fields of science and alumni work is at a close level.